Knowledge and Implementation of the DNR in Internal Medicine Teaching Programs - Ramírez Rivera, José; Cánova Díaz, Carlos; Hunter Mellado, Robert (Puerto Rico Health Sciences Journal, 2010)
Background: The knowledge and implementation skills of the DNR (do not resuscitate) order amongst physicians in training appears to be quite variable. Methods: We constructed, validated and implemented an instrument which evaluates knowledge and implementation skills of medical residents regarding the DNR in the 8 accredited teaching hospitals in Puerto Rico. Results: Participation of 136 residents from 240 approved positions was seen. Most thought (93.3%) the DNR should be written in the medical record. And 88.1% thought appropriate to suggest a DNR to the patient or family for a terminally ill patient. For a patient with an uncertain prognosis who insisted on a DNR , 78.5 % believed the attending physician and 21.5% thought the ethics committee was responsible for determining the propriety of the order. When the patient and the treating physicians agreed on the appropriateness of a DNR order most residents in the North of Puerto Rico thought the writing of the order was the purview of the resident while residents in the South-West thought this to be the responsibility of the attending physician. In the absence of a DNR order, more than 77.4% of the residents in the North and South would initiate CPR in a comatose patient with terminal cancer, multiple organ failure and sepsis in contrast to 15% of the residents in the West. Conclusions: Implementation and knowledge skills of medical residents in the health regions of Puerto Rico differ. Knowledge and implementation of the DNR merits improvement in all training programs.